PATHOLOGICAL LESIONS CAUSED BY PROFILICOLLIS ALTMANI (PERRY, 1942) VAN CLEAVE, 1947 (ACANTHOCEPHALA) IN A GRAY GULL (LEUCOPHAEUS MODESTUS) (TSCHUDI, 1843) FROM THE PERUVIAN COAST - Gonzales-Viera, Omar (2009)
Pathological lesions caused by acanthocephalans in marine birds are still little known. In this sense, a study of the pathological lesions in the gray gull (Leucophaeus modestus) (Tschudi, 1843) caused by theacanthocephalan Profilicollis altmani (Perry, 1942) Van Cleave, 1947 is presented. Gross lesions weremainly thickening of the intestinal wall in the area of deep penetration by the worm, with white serosalnodules. Microscopically was observed penetration from the parasite's anterior end in the villi andsubmucosa, surrounded by severe caseous necrosis and an inflammatory reaction composed by a moderate number of eosinophils and some multinucleated giant cells, mononuclear cells and peripherally a dense fibrous and vascularized connective tissue. Furthermore, the area between the proboscis and the necrotic tissue presented a number of bacilli basophilic bacteria. Additionally, in adjacent areas, necrotic focuses were observed surrounding by multinucleated giant cell forming small multifocal granulomas. These observations suggest that P. altmani causes severe eosinophilic granulomatous enteritis in the gray gull, a migratory bird common of the Peruvian coast.